Dosagem e otimização de misturas de concreto permeável por controle de porosidade pelo método do grau de compactação. - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2022)
Pervious concrete is a material with potential application in pervious pavements to mitigate urban flooding. The mixture design of pervious concrete is one of the fundamental steps for the development of mixtures with properties suitable for its application. Mixture design methods have been proposed in the literature, but their application is still limited. In this study the main objective was to propose a mixture design method adaptable to different coarse aggregate gradations and variable compaction energy. The proposed mixture design method was based on the coarse aggregate compaction state, allowing the development of mixtures with porosity control by the degree of compaction. This methodology was applied in the development of 48 mixtures of pervious concrete with porosities of 20, 25 and 30%, evaluating different coarse aggregate gradations, inclusion of fine aggregate and use of superplasticizer admixtures. Based on the degree of compaction method, it was possible to systematize a design process for pervious concrete to control its hydraulic and mechanical properties by porosity control. To apply the methodology, pervious concrete mixtures with porosity between 15 and 30% were developed. Models of compressive strength, hydraulic conductivity and cement consumption were developed as a function of porosity to allow the design of mixtures. For the porosity range analyzed it was possible to achieve strengths between 9.5 and 29.4 MPa and hydraulic conductivities between 0.07 and 1.55 cm/s. A second stage in the mixture design was proposed to optimize the pervious concrete mixtures for a target porosity. Methodologies were presented to change the w/c ratio and include fine aggregate with the objective of improving the mechanical strength and reducing the cement consumption of pervious concrete. By reducing the w/c ratio from 0.28 to 0.20 it was possible to obtain increases in compressive strength between 17 and 37% without harming the hydraulic performance of the mixture. The inclusion of 20% fine aggregate in the pervious concrete mixture made it possible to reduce cement consumption by approximately 10%, while maintaining the compressive strength and hydraulic conductivity. For mixtures with 20% porosity, the inclusion of 40% fine aggregate would still provide a 17% cement reduction without affecting its properties. Thus, for the materials evaluated in this study, the proposed design method allowed the development of mixtures with controlled porosity, also enabling the control of their mechanical and hydraulic properties. The proposed method also allowed the control of the w/c ratio and fine aggregate content in the mixture, being also possible to optimize the pervious concrete aiming a higher efficiency in cement consumption.
Keywords: Dosagem; Pavimento Permeável; Compactação; Agregado; Pasta de Cimento; Mixture Design; Pervious Pavement; Compaction; Aggregate; Cement Paste; CNPQ::ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA